Does it matter if immigrants work in jobs related to their education? - Jason Dean (IZA Journal of Development and Migration, 2018)
A common finding throughout the Canadian immigration literature is that, despite having high levels of education, recent immigrants endure substantial earnings disadvantages upon arrival that persist throughout their working career. This paper investigates the role of 'qualitative' education-job matches in explaining these poor labor market outcomes. Using a self-reported match measure, available in the Survey of Labour and Income Dynamics (SLID), the incidence and wage penalties associated with being mismatched are found to be higher among immigrants relative to Canadian-born workers. As a consequence, mismatches on the part of immigrants are a mechanism behind the immigrant wage disadvantages reported throughout the literature. Successful matching is also found to significantly improve the return to pre-migration education and work experience.
Keywords: I2; J3; 330; Immigrants; Returns; Education; Experience; Job match